Integrasi Pengelolaan Keuangan Dan Laporan Pertanggungjawaban Melalui Aplikasi Sakti (Studi Pada Perwakilan BPKP Provinsi Sumatera Barat) - Rita Hariani; Afridian Wirahadi Ahmad; Amy Fontanella (Journal of Applied Accounting And Business, 2024)
This research aims to see the impact on the use of the SAKTI application on the West Sumatra Province BPKP Representative as well as reviewing how the internal control system practices for the application so that it can provide good integration in the preparation of accountability reports and financial reports. The qualitative approach is the approach used in this research. There are several sources who are the core informants in this research, namely parties who directly use the SAKTI application for each module. The data collection process in this research used interviews, document reviews, and documentation related to the SAKTI application. The research results show that using the SAKTI application makes it very easy for BPKP representatives of West Sumatra Province to make accountability reports and financial reports. Apart from that, since the existence of the magic application, the internal control system over finances has become better